Etiological spectrum of infectious keratitis in the era of MALDI-TOF-MS at a tertiary care hospital - Rohilla, Ranjana (J Family Med Prim Care, 2020)
BACKGROUND: Infectious Keratitis (Ik) Is A Potential Vision-Threatening Ocular Infection Caused By A Variety Of Microorganisms. AIM: To Explore Risk Factors And Etiological Agents Associated With Ik. DESIGN: A Prospective Cross-Sectional Study In Which Corneal Scrapings From 120 Suspected Cases Were Evaluated At A Tertiary Health Care Institute From January To December 2019. METHODS: Scrapings Were Subjected To Direct Microscopy, Culture, And Identification By Both Conventional Methods And Maldi-Tof-Ms. The Patient's Demographic Data And Predisposing Factors, If Any Were Recorded. RESULTS: The Mean Age Of Patients Was 48.9 Years And Predisposing Factors Were Documented In 46% (55/120) Of Cases. Overall, Infective Etiology Could Be Established In 51% (N = 61/120) Of Cases. Fungal Growth In 26% (N = 31/120) Of Cases And Bacterial Growth In 22% (N = 27/120) Of Cases Was Obtained. Growth Of More Than One Species Of Fungi Or Growth Of Bacteria Along With Fungus Were Observed In 2% (N = 3/120) Of Cases. Of All The Fungal Isolates Obtained (N = 34), The Most Common Isolate Was Fusarium (18/34) Followed By Aspergillus (8/34), Curvularia (4/34), Pseudallescheria Boydii (3/34), And Geotrichum (1/34). Among The Gram-Positive Bacterial Isolates (N = 16), Staphyloccus Species (15/16) Were Isolated In Maximum Number Followed By Streptococcus Pneumoniae (1/16). Among The Gram-Negative Isolates (N = 13), Pseudomonas Species (8/13) Were Isolated In Maximum Number Of Cases, Followed By Acinetobacter (3/13), Klebsiella Pneumoniae (1/13), And Escherichia Coli (1/13). CONCLUSION: For Initiating Appropriate Empirical Therapy, The Knowledge Of The Epidemiological Pattern Of Infectious Keratitis Of A Particular Geographical Region Is Crucial.